OPTIMALISASI EKSTRAKSI DNA DAN PCR-RAPD PADA GREVILLEA SPP. (PROTEACEAE) - PHARMAWATI , MADE (Jurnal Biologi Udayana; Vol 13 No 1 (2009): JURNAL BIOLOGI, 2009)
Molecular genetic analysis of plants relies on high yield and high purity of DNA as well as optimized condition of molecular reactions. Appropriate methods for DNA extraction and molecular reactions such as PCR are therefore needed. This study aimed to develop protocol for extraction of high molecular weight DNA from Grevillea leaf and to optimize condition of PCR-RAPD. Standard plant DNA extraction of Doyle and Doyle was modified by increasing EDTA concentration to 50 mM and addition of 2% (v/v) 2-mercaptoethanol. Moreover, incubation time was prolonged to 14-16 h at 55oC. This method yielded good quality of DNA and consistent results. Amplification of DNA using PCR-RAPD will become efficient and consistent if the amplification reactions are in ideal condition. In Grevillea, clear, reproducible and scorable PCR-RAPD patterns were obtained using 10ng DNA template, 5 pmol primer, 2.5 mM MgCl2 and the number of thermal cycle was 40 x.
Keywords: DNA extraction- Grevillea, PCR-RAPD